Environmental circulation of the anthelmintic drug albendazole affects expression and activity of resistance-related genes in the parasitic nematode Haemonchus contortus - Dimunová, Diana; Matoušková, Petra; Navrátilová, Martina; Nguyen, Linh Thuy; Ambrož, Martin; Vokřál, Ivan; Szotáková, Barbora; Skálová, Lenka (The Science of the total environment, 2022)
Veterinary anthelmintics excreted from treated animals pass to soil, subsequently to plants and then to their consumers. This circulation might have various consequences, including drug-resistance promotion in helminths. The present study was designed to follow the effect of the environmental circulation of the common anthelmintic drug albendazole (ABZ) in real farm conditions on the parasitic nematode Haemonchus contortus in vivo. Two fields with fodder plants (clover and alfalfa) were fertilized, the first with dung from ABZ-treated sheep (at the recommended dosage), the second with dung from non-treated sheep (controls). After a 10-week growth period, the fresh fodder from both fields was used to feed two groups of sheep, which were infected with H. contortus. Eggs and adult nematodes from the animals of both groups were isolated, and various parameters were compared. No significant changes in the eggs' sensitivity to ABZ and thiabendazole were observed. However, significantly increased expression of several cytochromes P450 and UDP-glycosyl transferases as well as increased oxidation and glycosylation of ABZ and ABZ-sulfoxide (ABZ-SO) was found in the exposed nematodes. These results show that ABZ environmental circulation improves the ability of the helminths to deactivate ABZ.
Keywords: Sheep; léková rezistence; Drug resistance; Nematoda; Albendazole; zvířata; Haemonchus; Anthelmintics; UDP-glycosyl transferases; hlístice; Drug Resistance; anthelmintika; albendazol; Efflux transporters; Animals; Cytochromes P450; Micropollutants; Veterinary drugs; ovce